Legal Consequences For A Notary Public With Double Professions As A Rector Of A Private University Based On Law On Office Of Notary Public - Sri Walny Rahayu; Mohd. Din; Muhammad Suhail Ghifari; Rabi'ah Adawiyah Phonna Effendy Jaraputri (Universitas Islam Negeri Antasari Banjarmasin, 2023)
Abstract: This research discusses juridical consequences for a notary with double professions as a rector of a private university according to Law on office of notary public. The purpose of this research is to explore and analyze the juridical consequences and sanctions for a notary with double professions as a rector or lecturer of a private university according to Law on office of notary public and code of ethics. This is normative legal research. This research shows that Article 17 Letter f of UUJN explicitly mentions the prohibition for a notary to has double professions as a manager or an employee of a State-owned Enterprise, a Municipally-owned Corporation, or a private company. A notary public who becomes a rector or lecturer at a private university is not assumed to violate the provision of Article 17 letter f UUJN. However, a notary with double professions can get administrative sanction in the form of a written warning, temporary layoff, honorably or dishonorably discharge.Keywords: Doubling for a notary; Rector of Private University Abstrak: Penelitian ini membahas mengenai konsekuensi yuridis bagi notaris yang merangkap jabatan sebagai pimpinan perguruan tinggi swasta menurut undang-undang jabatan notaris. Penelitian ini bertujuan untuk mengkaji dan menganalisis mengenai konsekuensi yuridis serta penerapan sanksi bagi notaris yang merangkap jabatan sebagai pimpinan atau dosen di perguruan tinggi swasta menurut undang-undang jabatan notaris dan kode etik. Jenis Penelitian ini ialah penelitian yuridis normatif. Hasil Penelitian menunjukkan bahwa dalam Pasal 17 huruf f UUJN secara eksplisit disebutkan bahwa adanya larangan bagi pengemban profesi Notaris untuk merangkap jabatan sebagai pemimpin atau pegawai BUMN, BUMD atau badan usaha swasta. Seseorang yang mengemban jabatan Notaris menjadi pimpinan dan dosen pada Perguruan Tinggi Swasta tidak melanggar ketentuan Pasal 17 huruf f UUJN. Serta terkait notaris yang melakukan rangkap jabatan dapat dikenakan sanksi administratif berupa peringatan tertulis, pemberhentian sementara, pemberhentian dengan hormat atau tidak hormat.Kata Kunci: Rangkap Jabatan Notaris, Pimpinan Perguruan Tinggi Swasta.